Saturday
March 25, 2017

Post a New Question

Posted by on .

-4x+1-2(x-1)= -4(x-4)

  • Algebra - ,

    -4x+1-2(x-1)= -4(x-4)

    -4x + 1 - 2x + 2 = -4x + 16

    -6x + 3 = -4x + 16

    -2x = 13

    x = -6.5

  • Algebra - ,

    - 4 x + 1 - 2 ( x - 1 ) = - 4 ( x - 4 )

    - 4 x + 1 - 2 * x - 2 * ( - 1 ) = - 4 * x - 4 * ( - 4 )

    - 4 x + 1 - 2 x + 2 = - 4 x + 16

    - 4 x - 2 x + 1 + 2 = - 4 x + 16

    - 6 x + 3 = - 4 x + 16

    - 6 x + 4 x = 16 - 3

    - 2 x = 13 Divide both sides by - 2

    x = 13 / - 2 = - 13 / 2

    x = - 6.5

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question